Evolución Política y Partido Republicano. Trayectorias y discursos de la nueva derecha partidaria chilena - Durán Migliardi, Carlos Salvatore; Rojas Roa, Gabriel Eduardo (El Colegio de México A.C., 2021)
Based on the description of the Chilean sociopolitical context over the last decade, this article analyzes the origins, key discourses and configuration of the party identity of Evolución Política and Partido Republicano, parties of recent creation that belong to a regional context of renewal of the Latin American Right. The central hypothesis is that both parties arise from the search to face in different ways the challenges generated by the Right as a result of their return to government in 2010 and the dislocating effect of the social mobilizations of 2011.